Paraneoplastic immunoglobulin A nephropathy in a patient with lung adenocarcinoma: A case report and literature review. Issue 4 (April 2021) - Wang, Jing; Liu, Yang; Liu, Nian; Gao, Menghan; Yuan, Hang
Immunoglobulin A nephropathy (lgAN) is a common primary glomerulonephritis, but paraneoplastic IgAN has been rarely reported. This current case report describes a 49-year-old male patient that was referred with proteinuria, oedema and hypoproteinaemia after lung cancer surgery and before the first cycle of chemotherapy. Renal biopsy confirmed lgAN. The patient received four cycles of chemotherapy (first cycle: pemetrexed + nedaplatin; second to fourth cycle: pemetrexed + carboplatin). The symptoms of IgAN were gradually relieved with additional cycles of chemotherapy. At the latest follow-up on 10 February 2020, there was no evidence of lung cancer recurrence and all symptoms of lgAN had disappeared. lgAN combined with lung adenocarcinoma is quite rare, which suggests that IgAN might be a paraneoplastic manifestation of lung adenocarcinoma.